Evaluation of a child food reward task and its association with maternal feeding practices - Toh, Jia Ying (2021)
Food reward is defined as the momentary value of a food to the individual at the time of ingestion and is characterised by two psychological processes-"liking" and "wanting". We aimed to validate an age-appropriate food reward task to quantify implicit wanting of children from the GUSTO cohort (n = 430). At age 5 years, child appetitive traits and maternal feeding practices were reported by mothers via questionnaires. At age 6, a write-for-food task based on the child's preference for food or toy rewards was undertaken in laboratory conditions. Child BMI and skinfold measurements were taken at age 7. Convergent validity of the food reward task was assessed by associating with child appetitive traits, where enjoyment of food/food responsiveness (OR: 1.51; 95% CI: 1.06, 2.15) and emotional overeating (OR: 1.64; 95% CI: 1.09, 2.48) were positively associated with high food reward in children. Criterion validity was tested by associating with child BMI, however no significant relationships were observed. Multivariable logistic regression analysis with maternal feeding practices revealed that children whose mother tend to restrict unhealthy food (OR: 1.37; 95% CI: 1.03, 1.82) and girls whose mothers taught them about nutrition (OR: 2.09; 95% CI: 1.19, 3.67) were more likely to have high food reward. No further significant associations were observed between food reward, other appetitive traits and feeding practices. Despite the lack of association with child weight status, this study demonstrated the value of the write-for-food task to assess food reward in children and presented sex-specific associations with maternal feeding practices.